Epistaxis After Orthognathic Surgery: Literature Review and Three Case Studies. Issue 2 (June 2022) - Girard, Alisa; Lopez, Christopher D.; Chen, Jonlin; Perrault, David; Desai, Nikhil; Bruckman, Karl C.; Bartlett, Scott P.; Yang, Robin
Study Design: This is a literature review with 3 case studies. Objective: Intraoperative and postoperative bleeding are the most common complications of orthognathic surgery and have the potential to become life-threatening. The rarity of severe postoperative epistaxis has resulted in limited characterization of these cases in the literature. The purpose of this study is to 1) differentiate various presentations of epistaxis following orthognathic surgery in the literature, 2) identify management approaches, and 3) to synthesize a treatment algorithm to guide future management of postoperative epistaxis. Methods: A literature search of PubMed was conducted and 28 cases from 17 studies were assessed. Results: Bleeding within the first week may indicate isolated epistaxis, often resolved with local tamponade. Half of cases were attributed to pseudoaneurysm rupture (n = 14), with epistaxis onset ranging from postoperative day 6 to week 9. Angiography was used in most cases (n = 17), often as the primary imaging modality (n = 11). Nasal endoscopy is a less invasive and effective alternative to angiography with embolization. Proximal vessel ligation was used in 3 cases but is not preferred because collaterals may reconstitute flow through the defect and cause rebleeding. Repeat maxillary down-fracture with surgical exploration was described in 4 cases. Conclusions: As outlined in our management algorithm, nasal packing and tamponade should be followed by either local electrocautery or vascular imaging. Angiography with embolization is the preferred approach to diagnosis and management, whereas surgical intervention is reserved for cases of embolization failure or unavailability.